2016
DOI: 10.21037/tau.2016.08.20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of semen parameters during 2 weeks of daily ejaculation: a first in humans study

Abstract: BackgroundTimed and frequent intercourse around the time of female ovulation is recommended to improve conception. Although a significant number of articles have examined how the length of abstinence affects these semen analysis, the effects of frequent (daily) ejaculation has not been rigorously studied.MethodsTwenty normal men were recruited for daily ejaculation over 14 consecutive days, after a 3–5 days abstinence period. Semen samples were collected at the beginning of the study (day 1) and then on days 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Thus, there is a strong correlation between longer abstinence time and increased semen volume. [ 17 18 19 ] The total sperm concentration per ejaculate was highest in Group IV with maximum duration of abstinence. Many relevant studies have also demonstrated increase in total sperm count associated with longer abstinence time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a strong correlation between longer abstinence time and increased semen volume. [ 17 18 19 ] The total sperm concentration per ejaculate was highest in Group IV with maximum duration of abstinence. Many relevant studies have also demonstrated increase in total sperm count associated with longer abstinence time.…”
Section: Discussionmentioning
confidence: 99%
“…Many relevant studies have also demonstrated increase in total sperm count associated with longer abstinence time. [ 13 17 20 21 22 ] A few other studies reported the impact of frequent ejaculation (24 h) and found a fall in total sperm count, higher level of sperm chromatin immaturity with daily ejaculation, when compared to longer period of abstinence. [ 9 22 23 24 ] Total motile sperm concentration was highest in Group II with the abstinence period of 2–5 days with no significant difference from other groups.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of key findings based on multiple parameters can be found in Table 2. Fifteen of the 17 studies (88.2%) demonstrated that with longer abstinence, men can achieve statistically significant increases in overall semen volume [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Using a gradual scale based on specific definitions of abstinence provided by each study, no studies demonstrated decreases in semen volume with longer abstinence times.…”
Section: Semen Volumementioning
confidence: 99%
“…Welliver et al. () reported that the semen volume, total motile sperm count and sperm concentration were significantly decreased in normal men, with semen samples collected as daily ejaculated from day 1 (baseline) to days 3, 7 and 14 after 3–5 days of abstinence. However, motility, morphology and sperm DNA integrity did not change with SAP during the study.…”
Section: Discussionmentioning
confidence: 99%